Knockout rates across the states as a way of predicting injury and knockout based on fighter sex, weight, or experience - Twohey, E.; Velasco, G.; Neidecker, J.; Giovane, R. (The Physician and Sportsmedicine, 2024)
Combat sports, such as boxing and mixed martial arts [MMA], have the unique objective to finish a bout by way of knockout [KO] or technical knockout [TKO]. There are potentially both short- and long-term neurological injuries that can happen as a result of the repeated head trauma sustained in bouts, and thus it is imperative to identify the athletes that are at increased risk. Using an online database of professional boxing bouts [boxrec.com] over a 6-month period, KO/TKO rates were calculated across different states, weight classes, sex, and Fight Exposure Score [FES] categories. There was found to be a significant association between KO/TKO rates and weight class, sex, and FES category with heavyweights, males and FES 0 boxers having higher KO/TKO rates. KO/TKO rates were increased in winless boxers. KO/TKO rates across the states are documented in the study.